"Ampak to pa lahko pohvalimo, da je o miru in ljubezni spregovoril mohamedan": mobilizacija obmejnega orientalizma proti gradnji džamije v Ljubljani - Kalčić, Špela (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
ALAS IT IS COMMENDABLE THAT A MOHAMMADAN SPOKE ABOUT PEACE AND LOVE : MOBILISATION OF FRONTIER ORIENTALISM AGAINST THE CONSTRUCTION OF A MOSQUE IN LJUBLJANA. Discourses having appeared during the past few years in Slovenia in connection with the establishing of the Islamic religious and cultural center in Ljubljana, were successfully based upon the myths of the border orientalism (Gingrich 1998) about the Turkish raids into the territory of the present Slovenia in the Middle Ages. In these discourses, the Moslems in Slovenia were often simply equalled to medieval Turks , or they were attributed alleged cruelty, characteristic of their supposed medieval ancestors . Tales about Moslems and Turks were triggered by politicians, supported by media, and discussed by people from different ranks, from state officials, representatives of the Roman Catholic church, theologists, intellectuals to citizens, who took part in these discussions through media. The present article analyzes the use of myths of border orientalism, which were abused by different nationalis and islamophobic actors in the mobilization against the building of a mosque in Ljubljana, thus contributing to the construct of Otherness of Moslems in Slovenia.
Keywords: Slovenia; Slovenija; verske skupnosti; džamije; Muslim; muslimani; diskriminacija; ksenofobija